2012
DOI: 10.3357/asem.2893.2012
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Dive Exercise and Post-Dive Evolution of Venous Gas Emboli

Abstract: Cycling exercise prior to diving did not reduce the number of circulating VGE in comparison to control, in contrast to recent studies. A number of factors may be responsible for these findings, including type of exercise performed, wet diving experience, and disparity in Doppler measurement techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…The statistically insignificant change in BG following the exercise dive compared to the control dive is in line with previous research using similar open sea diving protocols. The impact of exercise on VGE is positive in some studies, although none of these can be directly compared to this experiment as they utilized simulated diving (Gennser et al ., ) or diving profiles that utilized decompressions stops (Castagna et al . 2011).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The statistically insignificant change in BG following the exercise dive compared to the control dive is in line with previous research using similar open sea diving protocols. The impact of exercise on VGE is positive in some studies, although none of these can be directly compared to this experiment as they utilized simulated diving (Gennser et al ., ) or diving profiles that utilized decompressions stops (Castagna et al . 2011).…”
Section: Discussionmentioning
confidence: 97%
“…The statistically insignificant change in BG following the exercise dive compared to the control dive is in line with previous research using similar open sea diving protocols. The impact of exercise on VGE is positive in some studies, although none of these can be directly compared to this experiment as they utilized simulated diving (Gennser et al, 2012) or diving profiles that utilized decompressions stops (Castagna et al 2011). One study with rats utilized a relatively extreme downhill running protocol (100 min at À16°) to induce myofibrillar damage and found no difference in bubble amounts or survival rates following a simulated dive (Jorgenson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the bubble grades observed following the supine control treatments (C1–C3) were surprisingly low. The dive profile chosen for the study (United Kingdom Royal Navy Table 11) has been used to provoke bubbles in a number of trials investigating prophylactic measures to guard against DCS ( Blogg et al, 2010 , 2017 ; Jurd et al, 2011 ; Gennser et al, 2012 ), as it is known to regularly produce VGE loads across the complete range of the KM grading scale, but with a low incidence of DCS. However, in the present study, hardly any bubbles were produced following the control HE.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this scarcity of bubbles is not known but could be explained to some extent by the fact that the subjects in the present study were all young and fit (mean age 23 and mean BMI 23.4), which is in contrast to other studies. For example in the study by Gennser et al (2012) , the mean age of the subjects was 40 years, with a mean BMI of 27.7. Further, Conkin et al (2003) found that age was significantly related to VGE load, with younger subjects having fewer bubbles.…”
Section: Discussionmentioning
confidence: 99%